Breast cancer development in rats under the influence of platelet factor-4 (PF4) and/or rapamycin - Yaman, Zaihassni Mat (2016)
Breast cancer is a leading cause of morbidity and mortality among women worldwide. Steroid hormone receptors such as Estrogen Receptor (ER) and Progesterone Receptor (PR) play a critical role in breast cancer growth. In this study, ER and PR were selected as markers for steroid receptor determination due to the strong association between breast cancer development and the influence of steroid hormones as demonstrated in many studies. On the other hands, the Peroxisome Proliferator Activation Receptor γ (PPARγ), a family of nuclear hormone receptor was also determined as it was a potential effector for tumour cell differentiation. Rapamycin, a drug from bacteria microlide and Platelet Factor-4 (PF4), a plateletderived chemokine have anticancer properties. Therefore, it will be interesting to analyse the effect of Rapamycin and PF4 in blocking the growth of breast cancer from responding to hormone stimulation. In this study, invasive mammary carcinoma was induced with 70mg/kg body weight 1-Methyl-1-Nitrosourea (MNU) in 80 young female Sprague Dawley rats. The gene and protein expressions of ER, PR and PPARγ markers were evaluated by using semiquantitative immunohistochemistry analysis and quantitative real-time PCR assay. Findings from the untreated-control group demonstrated that all mammary lesions are 100% malignant, histopathologically characterized with invasive ductal carcinoma (IDC) of three major type ie. cribriform, papillary and Not Otherwise Spesified (NOS). Rapamycin treatment showed significant inhibition of mammary tumour progression as well as reduction of tumour agressiveness. Even though treatment with Rapamycin significantly overexpressed ER and PR , activation of PPARγ promotes differentiation of tumour cells which lead to a more differentiated mammary tumour and consequently reversing the aggressive phenotype of the lesion. Meanwhile, treatment with PF4 did not regress tumour growth and consequently showed no significant expression of ER, PR and PPARγ. Upregulation of all these three markers in combination treatment lead to significant tumour regression and phenotypically decreased aggressiveness. It was predicted that Rapamycin predominantly showed anticancer effect rather than PF4. Thus, present findings suggested that Rapamycin is neither synergistic nor additive with PF4. It was concluded that Rapamycin is a potent anticancer agent for breast cancer because it halt tumour growth and thus promote tumour cells differentiation through a positive expression of hormone receptors analysis. Further study will be needed to analyse the regulation of ER isoforms ( ERα and ERβ ) and PR isoforms ( PR-A and PR-B) to improve potential therapeutic strategy in breast cancer treatment through anticancer effects of Rapamycin.